2022
DOI: 10.1007/s00445-022-01569-1
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation delay in water-saturated rhyolite during decompression in shallow volcanic systems and its implications for ascent dynamics

Abstract: We developed a model of feldspar nucleation delay during decompression in water-saturated rhyolite based on classical nucleation theory (CNT). With the thermodynamic and kinetic parameters proposed in this study, the model agrees with the experimental results of this study to within a factor of two. To account for the variety of conditions encountered by magma during ascent, we propose expanding the model, developed in this study for isothermal decompression, to a wider range of pressures and temperatures (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Indeed, we suggest that nucleation delay in many common magmatic melts can now be modeled by combining classical nucleation theory [2], thermodynamic models of plagioclase, quartz, olivine, and clinopyroxene crystallization [61], our knowledge of Si-Al interdiffusion in silicate melts, and silicate-melt interfacial energies [13]. Although these calculated delays may not be exact, a combination of the nucleation delay time with detailed petrographic observations may provide important constraints on the times available for crystallization during processes such as intrusion of a hot magma into cold country rocks, extrusion on to the surface of a planet, ascent and undercooling of hydrous magmas in magmatic conduits, and any other magmatic process where a magma is rapidly cooled to subliquidus conditions (e.g., [5,25]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, we suggest that nucleation delay in many common magmatic melts can now be modeled by combining classical nucleation theory [2], thermodynamic models of plagioclase, quartz, olivine, and clinopyroxene crystallization [61], our knowledge of Si-Al interdiffusion in silicate melts, and silicate-melt interfacial energies [13]. Although these calculated delays may not be exact, a combination of the nucleation delay time with detailed petrographic observations may provide important constraints on the times available for crystallization during processes such as intrusion of a hot magma into cold country rocks, extrusion on to the surface of a planet, ascent and undercooling of hydrous magmas in magmatic conduits, and any other magmatic process where a magma is rapidly cooled to subliquidus conditions (e.g., [5,25]).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple variations of Equation ( 3) have been derived; each variant of the equation provides a slightly different estimate of the nucleation delay (e.g., [55][56][57][58]). Equation ( 3) was chosen for this study because of its previously demonstrated success in the prediction of nucleation delay times [5,25,59].…”
Section: Calculation Of Nucleation Delay Using Classical Nucleation T...mentioning
confidence: 99%
See 1 more Smart Citation
“…DOI: https://doi.org/10.2138/am-2022-8765. http://www.minsocam.org/ 2013; Polacci et al 2018;Le Gall et al 2021;Arzilli et al 2022), nucleation delay (Arzilli et al 2020;First et al 2020;Rusiecka et al 2020;Rusiecka and Martel 2022), and crystal growth in real time (Polacci et al 2018;Arzilli et al 2019Arzilli et al , 2022Le Gall et al 2021).…”
Section: Introductionmentioning
confidence: 99%